Orthodontic treatment after occlusal intervention balances osteoblast and osteoclast differentiation via SIRT1 beta catenin signaling in rats with hypofunctional occlusion - Juanjuan Ji; Zhi Zhou; Yaling Zhu; Rui Wang; Yali Liu (Scientific Reports)
Abstract Orthodontic treatment can enhance occlusal force, yet it may increase the sensitivity of periodontal tissues. To compare the impacts of orthodontic treatment, intervention, and combined treatment (intervention first, then orthodontics) on alveolar bone remodeling, we established a rat model with low occlusal function. Three weeks after combined treatment, the levels of BMP2 and BGP increased by approximately 36% and 78% respectively, and the changes were even more remarkable after 4 weeks. Meanwhile, the expression of CTSK was inhibited, while the expression of OPN and RUNX2 increased. From the second to the third week, the key proteins in the SIRT1/β - catenin pathway underwent changes. At 4 weeks, the expression of SIRT1 and β - catenin increased by around 73% and 60% respectively. This study indicates that the combined treatment alleviates the side effects of orthodontics. Orthodontic force may activate the β-catenin pathway via SIRT1 to balance alveolar bone osteogenesis and osteoclast differentiation. This research provides a targeted treatment strategy and a theoretical basis for treating teeth with low occlusal function. It will contribute to optimizing clinical treatment outcomes, reducing the risk of periodontal tissue damage, and improving the prognosis of orthodontic treatment for patients.